2006
DOI: 10.1038/nature04585
|View full text |Cite|
|
Sign up to set email alerts
|

Oncogenic activity of Cdc6 through repression of the INK4/ARF locus

Abstract: The INK4/ARF locus encodes three tumour suppressors (p15(INK4b), ARF and p16(INK4a)) and is among the most frequently inactivated loci in human cancer. However, little is known about the mechanisms that govern the expression of this locus. Here we have identified a putative DNA replication origin at the INK4/ARF locus that assembles a multiprotein complex containing Cdc6, Orc2 and MCMs, and that coincides with a conserved noncoding DNA element (regulatory domain RD(INK4/ARF)). Targeted and localized RNA-interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
172
1
17

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(204 citation statements)
references
References 28 publications
14
172
1
17
Order By: Relevance
“…However, deregulation of the licensing system may also be a primary driver of oncogenesis, at least in some tumour types. For example, over-expression of Cdc6 or Cdt1 have been shown to be oncogenic, and deregulated Mcm7 expression has been linked to tumour formation, progression and malignant transformation in animal models [84][85][86][87][88][89][90]. Oncogenic mutations in genes upstream of the licensing machinery (eg RAS, CYCLINE and CYCLIND1 ) can also impact on tumourigenesis by causing deregulation of the licensing machinery.…”
Section: Dna Replication Licensing and Cancermentioning
confidence: 99%
“…However, deregulation of the licensing system may also be a primary driver of oncogenesis, at least in some tumour types. For example, over-expression of Cdc6 or Cdt1 have been shown to be oncogenic, and deregulated Mcm7 expression has been linked to tumour formation, progression and malignant transformation in animal models [84][85][86][87][88][89][90]. Oncogenic mutations in genes upstream of the licensing machinery (eg RAS, CYCLINE and CYCLIND1 ) can also impact on tumourigenesis by causing deregulation of the licensing machinery.…”
Section: Dna Replication Licensing and Cancermentioning
confidence: 99%
“…5 It has also been related to leukemias that involve PML-RARA chromosomal translocations 6 and other types of cancer, probably through a direct role in overreplication 7 or silencing of the tumor suppressor Ink4a. 8 CDC6 expression is also differentially regulated during physiological endoreplication of plants, 9 and previous work in our laboratory showed that CDC6 expression is actively maintained upon cell cycle exit following terminal megakaryocytic polyploidization. 10 This endoreplication-related expression appears to be independent on E2F binding sites.…”
Section: Cdc6 Has An Additional Important Rolementioning
confidence: 99%
“…Gonzalez et al [19] ont décrit un méca-nisme similaire liant la répression du locus Ink4a/Arf/Ink4b et la réplication de l'ADN. Ces auteurs ont identifié une origine de répli-cation à proximité immédiate du locus INK4, qui permet la répression de p16, p19 et p15 et qui est dépendante du recrutement de cdc6 associée aux autres protéines de la réplication.…”
Section: Répression Du Locus Ink4a/arf/ink4b Par Cdc6unclassified